Internet marketing tools - Sturienė, Urtė (Vilnius University Open Series, 2019)
In today's world, every business organization can pursue marketing goals online. Choosing the right Internet marketing tools or combining several may be significant in reaching the target audience. Therefore, without precise criteria for assessing the impact of Internet marketing tools on business organizations, it is not very easy to choose the most appropriate tools to compete with other businesses. This paper aims to investigate the impact of Internet marketing tools on business organizations. In order to achieve this goal, the following tasks are set: to analyse the Internet marketing concept and to reveal the impact assessment criteria. The results have shown that there is no agreed scientific definition of the term and concept of Internet marketing tools. However, it is obvious that Internet marketing is the part of digital marketing. Also, the Internet marketing impact criteria consist of short-term effect, long-term effect, and alternatives. Internet marketing tools typically drive sales growth, strengthen the brand and help to build and maintain relationships with clients.
Keywords: Internet marketing; Internet marketing tools; impact of Internet marketing